(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2025)
This study investigates the therapeutic potential of herbal extracts to mitigate bone marrow damage during DMBA-induced breast cancer and its treatment in rats. Untreated tumor-bearing rats showed elevated arginase activity and malondialdehyde (MDA) levels with reduced nitric oxide (NO) bioavailability. Treatment with herbal extract combined with the arginase inhibitor nor-NOHA, significantly reduced MDA and restored NO levels, demonstrating antioxidant and protective effects on the bone marrow. Conversely, combining a NOS inhibitor (L-NAME) with herbal extract exacerbated oxidative damage. The findings support using specific phytotherapeutics as adjuvants to conventional cancer therapy to maintain bone marrow integrity.